Enhancing the Classical Closed-Loop Algorithm in terms of Power Consumption - Rahman Mirzaei; Seyed Sina Kourehli (Advances in Civil Engineering)
An approach is suggested to reduce the peak and average control forces of actively controlled structures. In this method, responses of an actively controlled building should be much smaller than the responses of the same building controlled by the similar passive control mechanism. This approach leads to a time varying gain matrix, which is not restricted by external excitation but it is related to the selection of a scalar function. Extensive numerical analyses by using various scalar functions show that the proposed strategy effectively can reduce the need of the required control force consumptions.